Behind the curtain: External Examiners’ Experiences about Thesis Evaluation - Tiwari , Hari Prasad (Shanti Journal, 2024)
Evaluating a thesis is important because it ensures that students’ research is valuable and meets high academic standards before they are awarded their degrees. The study aimed at exploring the experiences of university-level English teachers as external examiners for Master of Education (M.Ed.) theses in English Education at the Faculty of Education (FoE), Tribhuvan University (TU). Sample population this qualitative study consisted of 17 University-level English Education teachers who worked as external examiners to evaluate the theses written by M.Ed. students specialized in English Education. The researcher employed judgmental sampling to select the sample. He used semi-structured interview technique to collect the data. The data was analyzed employing thematic approach of qualitative data analysis. Findings revealed several systemic issues in the thesis evaluation process. Participants noted thesis evaluation as ritualistic practices where procedures often became routine. This leads to inconsistencies and compromised evaluation quality. Supervisors' unfamiliarity with thesis writing guidelines prepared by Foe created further challenges. This unfamiliarity also affects feedback quality and evaluation standards. The study also identified variability in thesis quality, difficulties in integrating feedback, and ethical concerns, such as requests for biased evaluations. Time constraints emerged as a critical issue which limits the depth of review and feedback. Additionally, misalignment between examiner expectations and institutional requirements, along with inadequate institutional support, further complicated the evaluation process. These findings underscore the need for a re-examination of evaluation practices, enhanced training for supervisors, and improved institutional support to ensure a fair, consistent, and effective thesis evaluation process.